Camellia ngheanensis (Sect. Chrysantha: Theaceae), a new species from Central Vietnam - Do, Ngoc-Dai; Luong, Van-Dung; Le, Thi-Huong; Nguyen, Danh-Hung; Nguyen, Thanh-Nhan; Ly, Ngoc-Sam (Phytotaxa, 2020)
Camellia ngheanensis, a new species of Theaceae, is described and illustrated from Nghe An Province, Central Vietnam. It is most similar to C. ninhii in pubescent hairs on twigs and abaxial leaf blades, colour of flowers, pubescent ovary, glabrous filament, free styles from the base but differing by the glabrous petioles, pubescent bracteoles, 5-pubesncent sepals, 12 or 13 pubescent petals, and pubescent styles. The comparison between the new species and C. euphlebia,  C. petelotii, and C. velutina is presented. Data on ecology, phenology, vernacular name and uses, expected conservation status are given along with an illustration and a coloured plate.